A 3-Year Perspective on the Impact of a Multicultural Counseling Specialist. Issue 4 (1st October 2020) - Gomez, Judelysse; White, Bryana; Zakriski, Audrey; Spoltore, Janet Dee
ABSTRACT: Underrepresented and underserved college students encounter unique challenges and barriers influencing their mental health and treatment utilization. Responding to national and local student-led demands, we hired a Multicultural Counseling Specialist (MCS) at our student counseling center. This article describes the implementation of the MCS position on our PWI campus and provides a preliminary assessment of its impact. Results showed increased utilization by underrepresented students after MCS hire. Satisfaction data showed treatment satisfaction among all students. Black students reported higher counselor quality, and Students of Color were more likely to reference issues related to cultural competence, than their White peers.